Hatching success rate of sea turtle in the north coast of Pinrang Regency, South Sulawesi - Nyompa, Achmad Husein; Sulaeman, Haura Ainun; Masykur, Septian Fakhrulwahid; Bahri, Muhammad; Ayustina, Ratih (Journal of Earth Kingdom, 2024)
Background: Turtles are endangered marine reptile species due to various factors, including hunting, habitat loss, and predation. Therefore, practical conservation efforts are essential to protect turtle populations. One effective conservation strategy is to transfer turtle eggs to safe semi-natural nests. Method: This study was conducted in Turtle Village, Pinrang Regency. Leatherback and Green Turtle eggs were collected from natural nests along the coast and transferred to semi-natural nests. Observations were made to measure the hatching success rate of the eggs, and factors such as temperature, incubation period, predators, microorganism development, and changes in egg position were also recorded and analyzed. Findings: The results showed that the hatching success rate of eggs in semi-natural nests reached 80.23%. The highest hatching percentage was 86.36%, and the lowest was 68.33%. Factors that influenced hatching success included temperature and incubation period while hatching failure was caused by predators, microorganism development, and changes in egg position. Conclusion: This study shows that semi-natural nests in Turtle Village have a high hatching success rate with supportive environmental conditions and proper egg transmission. This indicates that conservation efforts through egg transfer to semi-natural nests can effectively increase turtle populations. Novelty/Originality of this study: It contributes to turtle conservation by demonstrating the effectiveness of semi-natural nests in increasing the hatching success rate of Leatherback and Green Turtle eggs. This approach can serve as a model for turtle conservation programs in other areas facing similar challenges.